Reverend Randy Hill and woman - Ted Sahl (photographer):::Creator::::::::::::
Photograph shows Reverend Randy Hill and a woman standing in front of a stained glass window. They are probably in a church. The Reverend is wearing an alb and stole and the woman is wearing a stole over street clothes. The stained glass window is depicting Christ accepting little children and has a plaque engraved with "Roy S. Herrold" below it.